Rapid transfer of photosynthetic carbon through the plant-soil system in differently managed species-rich grasslands - G. B. De Deyn; H. Quirk; S. Oakley; N. Ostle; R. D. Bardgett (Biogeosciences, 2011)
Plant-soil interactions are central to short-term carbon (C) cycling through the rapid transfer of recently assimilated C from plant roots to soil biota. In grassland ecosystems, changes in C cycling are likely to be influenced by land use and management that changes vegetation and the associated soil microbial communities. Here we tested whether changes in grassland vegetation composition resulting from management for plant diversity influences short-term rates of C assimilation and transfer from plants to soil microbes. To do this, we used an in situ 13C-CO2 pulse-labelling approach to measure differential C uptake among different plant species and the transfer of the plant-derived 13C to key groups of soil microbiota across selected treatments of a long-term plant diversity grassland restoration experiment. Results showed that plant taxa differed markedly in the rate of 13C assimilation and concentration: uptake was greatest and 13C concentration declined fastest in Ranunculus repens, and assimilation was least and 13C signature remained longest in mosses. Incorporation of recent plant-derived 13C was maximal in all microbial phosopholipid fatty acid (PLFA) markers at 24 h after labelling. The greatest incorporation of 13C was in the PLFA 16:1ω5, a marker for arbuscular mycorrhizal fungi (AMF), while after 1 week most 13C was retained in the PLFA18:2ω6,9 which is indicative of assimilation of plant-derived 13C by saprophytic fungi. Our results of 13C assimilation and transfer within plant species and soil microbes were consistent across management treatments. Overall, our findings suggest that plant diversity restoration management may not directly affect the C assimilation or retention of C by individual plant taxa or groups of soil microbes, it can impact on the fate of recent C by changing their relative abundances in the plant-soil system. Moreover, across all treatments we found that plant-derived C is rapidly transferred specifically to AMF and decomposer fungi, indicating their consistent key role in the cycling of recent plant derived C.